The Study of Tourist Behavior of Nakhon Nayok Province, Year 2019 - Koograsang, Apisak (Academic Journal Phranakhon Rajabhat University, 2021)
The study’s objectives for the tourists’ perception of tourism image and tourist behaviour after tourism in Nakhon Nayok Province. As part of the data collection area under the Rajabhat University Strategy for Sustainable Local Development in Nakhon Nayok Province, 2019. Activities to promote knowledge networks for community relations missions to solve integrated tourism problems. This study used quantitative research methods and questionnaire research tools. The population group is Nakhon Nayok tourists of 3 million people (Nakhon Nayok Provincial Statistical Office, 2019). Sampling was randomised without using a probability and randomly selected samples. The 402 subjects analysed the findings using percentage and mean statistics. Which the research results showed: General information about tourists is Thai and foreign tourists. Travelling with friends and family: Have a single and aged status between 31-40 years, undergraduate and work in a company with an income of 15,001-20,000 Baht per month, residing in the central region, Bangkok and its vicinity. The behaviour of tourists covered the areas studied as follows: number of times per year, the number of participants, travel planning time before the trip, number of nights average, accommodation cost, type of accommodation, season selected in travel, vehicle type, popular attraction type, activity in attraction including tourism objectives and tourism information. The tourists’ perceptions towards the tourism image of Nakhon Nayok Province in terms of tourism management, general issues, safety issues, inspiration, and feelings of tourist attractions and services. Tourist behaviour after tourism in the area of repeat tourism, feelings of understanding, sharing experiences, interest in tourism news, areas to improve, conditions, problems, and satisfaction levels with tourism.